New insights into the Sn underpotential deposition on Au(100) - Meier, Lorena Alejandra (2012)
The underpotential deposition (UPD) of Sn in the system Au(100)/Sn2+, SO42− has been studied by classical electrochemical techniques and in situ scanning tunneling microscopy. The results show that the Sn UPD initiates at relatively high potentials with the formation of a quasi‐hexagonal structure characterized as Au(100) − (√2 × 7)R45°. This expanded overlayer contributes to the modification of the surface morphology which exhibits flat terraces with step edges showing angles of 60 or 120°. At lower potentials two‐dimensional (2D) islands are formed which tend to grow, causing a coverage increase. In the underpotential region close to the formation of the 3D bulk phase the long time polarization experiments indicate the formation of different Au–Sn alloy phases.